Pola penggunaan insulin pada pasien diabetes mellitus tipe 2 di poli penyakit dalam RSU Negara Periode Juli - Agustus 2018 - Komang ayu Vitriana Gamayanti; Ni Luh Made Novi Ratnasari; Agha Bhargah (DiscoverSys Inc., 2018)
Aim: This study aims to determine the pattern of insulin therapy in type 2 Diabetes Mellitus patient in Internal Medicine Policlinic Negara Hospital, Bali.Method: This research was an observational study with cross-sectional design at Internal Medicine Policlinic Negara Hospital, Bali period August 2018. A total of 177 samples were selected by total sampling technique.Result: According to the duration of action, majority of insulin usage was rapid acting insulin in 93 patients (52,5%). The most frequent combination of two insulin types was long-acting with rapid-acting insulin in 30 patients (33,7%), meanwhile the Â most frequent combination of insulin and OHD was premixed insulin with gluconeogenesis inhibitor in 43 patients (48,9%). Fasting Plasma Glucose mean was 185,12 mg/dL, Post Prandial Plasma Glucose mean was 252,9 mg/dL. This study also found the Fasting Plasma Glucose â‰¥ 126 mg/dL count in 129 patients (72,9%), Post Prandial Plasma Glucose â‰¥ 180 mg/dl count in 133 patients (75,1%). The mean of systolic blood pressure was 128,81/ 78,53 mmHg, patients with targeted blood pressure <140/90 mm/Hg count in 110 patients (62,1%).Conclusion: The profile of insulin therapy in patients with Type 2 DM at Internal Medicine Polyclinic, Negara Hospital varies according to the indication in each patient. The most frequent type of insulin use is rapid acting insulin. Most patients with insulin therapy have not achieved targeted glycemic control, but have achieved the targeted blood pressure according to the PERKENI.